Comparative Analysis of Outcome Between Extravesical and Transvesical Repair for Vesicovaginal Fistula - Adnan Ali; Khubaib Shehzad; Zahoor Iqbal Mirza; Hussain Ahmed; Shazia Tabassum; Nisarefatima Changezi (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the surgical outcome of extravesical and transvesical repair of Vesicovaginal fistula.